2018
DOI: 10.1016/j.jcf.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of energy-dense, nutrient-poor and nutrient-dense food sources in children with cystic fibrosis

Abstract: The energy- and fat-dense CF diet is primarily achieved by overconsumption of EDNP foods, rather than ND sources. This dietary pattern may not be optimal for the future health of children with CF, who are now expected to survive well into adulthood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 23 publications
4
66
1
1
Order By: Relevance
“…Therefore, whether and how the CF GI dysbiosis contributes to disease progression, and the causes of the dysbiosis itself, are unclear [15,18]. Furthermore, people with CF consume more high-energy and high-fat diets compared to controls [19] and are frequently prescribed antibiotics and antifungal drugs to treat their lung infections, therapies that likely further disturb the gut microbiome in these patients. Additionally, as patients with CF live longer, they are at increased risk of developing cancers in the gastrointestinal tract, diseases with known relationships with the GI microbiome and inflammation outside of CF [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, whether and how the CF GI dysbiosis contributes to disease progression, and the causes of the dysbiosis itself, are unclear [15,18]. Furthermore, people with CF consume more high-energy and high-fat diets compared to controls [19] and are frequently prescribed antibiotics and antifungal drugs to treat their lung infections, therapies that likely further disturb the gut microbiome in these patients. Additionally, as patients with CF live longer, they are at increased risk of developing cancers in the gastrointestinal tract, diseases with known relationships with the GI microbiome and inflammation outside of CF [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…However, families may rely on energy‐dense but nutrient poor (EDNP) foods rather than nutrient‐dense foods to meet dietary goals. A cross‐sectional study of children with CF aged 2 to 18 years and age‐ and sex‐matched controls assessed dietary intake using the Australian Child and Adolescent Eating Survey (ACAES) food frequency questionnaire . Eighty children with CF and a mean age of 9.3 years consumed significantly more EDNP foods than controls with a mean age of 9.8 years, as assessed by both total energy (median [IQR] 1301 kcal/d [843‐1860] vs 686 [480‐1032]; P < .0001) and proportion of energy intake (median [IQR] 44% [34‐51] vs 31% [24‐43]; P < .0001).…”
Section: Multisystem Effects Of Cystic Fibrosismentioning
confidence: 99%
“…A crosssectional study of children with CF aged 2 to 18 years and age-and sex-matched controls assessed dietary intake using the Australian Child and Adolescent Eating Survey (ACAES) food frequency questionnaire. 48 Eighty children with CF and a mean age of 9.3 years consumed significantly more EDNP foods than controls with a mean age of 9.8 years, as assessed by both total energy Sufficient levels of vitamin D may improve pulmonary health by inducing the antimicrobial peptides cathelicidin (LL-37) and human-beta-defensin-2 (HBD-2). This was studied by obtaining bronchoalveolar lavage fluid (BALF) for and blood in children with and without CF undergoing fiberoptic bronchoscopy.…”
Section: Nutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy and macronutrient intakes (particularly fat) in patients with CF have been extensively explored however micronutrient intake in CF has not been as frequently or comprehensively investigated. A contemporary study by this group has previously reported that children with CF, especially those of school age, consume significantly more energydense, nutrient-poor foods than their age-matched controls [ 12 ]. This dietary pattern together with impaired digestion, malabsorption and increased nutrient utilization, highlights the potential difficulty children with CF may have in achieving optimal micronutrient status.…”
Section: Introductionmentioning
confidence: 95%